Counterparty risk management framework: theoretical approach in COVID-19 environment - Teresiene, Deimante; Gudaviciute, Beatrice (Technium Social Sciences Journal, 2021)
Counterparty risk is the most significant part of the credit risk. Credit risk can be explained by two different types of risk: issuer risk and counterparty risk. The importance of counterparty risk increased in the COVID-19 pandemic as lots of counterparties have met difficult economic conditions. This article presents the main issues related to the counterparty risk. Firstly, we try to identify the main concept of counterparty risk by analyzing different scientific views. We present various aspects of counterparty risk and we try to point how a counterparty risk should be understood in the context of credit risk. Then we make a short analysis of changes in credit quality and finally, we offer a framework for counterparty risk management. According to the latest data, we see a high probability of counterparty risk increase, especially in the energy and finance sectors. So because of that counterparty risk management framework is very important for every institution. Despite sometimes it can require higher costs for counterparty risk monitoring, every organization taking into account financial abilities must choose the right way for counterparty risk management.